TEKNIK PENERAPAN LESSON STUDY BAGI GURU SEKOLAH DASAR UNTUK MENINGKATKAN KUALITAS PROSES PEMBELAJARAN MAHASISWA PPL FKIP UNRAM - Dadi Setiadi; Nur Lestari; Mahrus Mahrus (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2021)
Many efforts have been made to improve the quality, one of which is lesson study. The service activities aim to make teachers comprehensively understand the concepts, advantages of lesson study, and be skilled in planning, implementing and evaluating lesson study reflections. This service emphasizes practice and is mentoring so that participants are more interested in participating in activities because the provision of assistance or guidance is more personal. The steps of service activities are as follows: (1) preparation stage; (2) implementation stage; (3) the stage of mentoring and monitoring; (4) evaluation and reporting stage. With an implementation model that is more based on direct classroom practice by participants, it is more likely that participants are skilled in carrying out lesson study and can be sustainable, including being applied in mentoring students participating in PPL FKIP UNRAM. The results showed that the participants were enthusiastic about participating in the service and understood well and comprehensively about the basic concepts of lesson study, had a good understanding of the advantages of implementing lesson study to improve the learning process, teachers had a good understanding of the techniques of implementing lesson study in schools, skilled in planning, implementing and evaluating and reflecting on the implementation of lesson study.